Strain hardening by dynamic slip band refinement in a high-Mn lightweight steel. (1st September 2016) - Welsch, E.; Ponge, D.; Hafez Haghighat, S.M.; Sandlöbes, S.; Choi, P.; Herbig, M.; Zaefferer, S.; Raabe, D.
Abstract: The strain hardening mechanism of a high-Mn lightweight steel (Fe-30.4Mn-8Al-1.2C (wt%)) is investigated by electron channeling contrast imaging (ECCI) and transmission electron microscopy (TEM). The alloy is characterized by a constant high strain hardening rate accompanied by high strength and high ductility (ultimate tensile strength: 900 MPa, elongation to fracture: 68%). Deformation microstructures at different strain levels are studied in order to reveal and quantify the governing structural parameters at micro- and nanometer scales. As the material deforms mainly by planar dislocation slip causing the formation of slip bands, we quantitatively study the evolution of the slip band spacing during straining. The flow stress is calculated from the slip band spacing on the basis of the passing stress. The good agreement between the calculated values and the tensile test data shows dynamic slip band refinement as the main strain hardening mechanism, enabling the excellent mechanical properties. This novel strain hardening mechanism is based on the passing stress acting between co-planar slip bands in contrast to earlier attempts to explain the strain hardening in high-Mn lightweight steels that are based on grain subdivision by microbands. We discuss in detail the formation of the finely distributed slip bands and the gradual reduction of the spacing between them, leading to constantly high strain hardening. TEM investigations of the precipitation state in the as-quenched state show finely dispersed atomically ordered clusters (size < 2 nm). The influence of these zones on planar slip is discussed. Graphical abstract: